Analysis of Adherence to Antihypertensive Drugs in Chinese Patients with Hypertension: A Retrospective Analysis Using the China Health Insurance Association Database - Cui B (Patient Preference and Adherence, 2020)
Bin Cui,1 Zhaohui Dong,2 Mengmeng Zhao,3 Shanshan Li,4 Hua Xiao,4 Zhitao Liu,4 Xiaowei Yan5 1School of Public Health, Peking University, Beijing 100191, People’s Republic of China; 2Human Resources and Social Security, Chinese Academy of Labour and Social Security, Beijing, 100029, People’s Republic of China; 3School of Pharmaceutical Science and Technology, School of Pharmacy, Tianjin University, Tianjin, 300072, People’s Republic of China; 4Medical Affairs, Bayer Healthcare Company Limited (China), Beijing, 100020, People’s Republic of China; 5Department of Cardiology, Peking Union Medical College Hospital, Beijing, 100730, People’s Republic of ChinaCorrespondence: Xiaowei YanPeking Union Medical College Hospital, Beijing 100730, People’s Republic of ChinaEmail yanxiaowei2019@gmail.comObjective: To analyze the adherence to antihypertensive drugs in Chinese patients with hypertension and the factors associated with the drug adherence.Methods: The data for this analysis were obtained from the 2014 China Health Insurance Association (CHIRA) database. The study included 64,576 patients aged ≥ 18 years who were prescribed one of the seven antihypertensive drugs included in the study in their first prescription in 2014 and were observed for ≥ 180 days. The medicine possession ratio (MPR) was calculated and taken as the measure of treatment adherence. MPR values < 0.3, 0.3 to < 0.5, 0.5 to < 0.8, and ≥ 0.8 were considered treatment adherence very low, low, intermediate, and high, respectively. Descriptive statistics were used to present baseline data and treatment adherence rate. Multiple regression models were used to determine independent factors which can affect the treatment adherence rate. P-value < 0.05 was considered significant.Results: Among the study antihypertensive drugs, amlodipine (33.98%), metoprolol (25.04%), and nifedipine (17.15%) were the frequently prescribed drugs. Nifedipine controlled release tablet had the highest MPR (0.61), followed by valsartan (0.53), valsartan/amlodipine fixed-dose combination (0.50), indapamide (0.40), and amlodipine (0.39), whereas benazepril (0.27) and metoprolol (0.19) had the lowest MPR. Higher reimbursement ratio, regular tertiary hospitals visits, lower age, and lower daily medical cost positively affected treatment adherence, whereas longer duration of illness and higher daily average cost affected treatment adherence negatively.Conclusion: Our study assessed that prescribing more cost-effective, long-acting antihypertensive drugs, and raising the reimbursement ratio were associated with a better treatment adherence in Chinese patients with hypertension.Keywords: treatment adherence, medicine possession ratio, hypertension, antihypertensive treatment